Fort Collins veterinary practices and websites: how telemedicine is used as a marketing tool - Weaver, Alice Malia, author; Seel, Pete B., advisor; Champ, Joseph, advisor; Rollin, Bernard, committee member (Colorado State University. Libraries, 2012)
This thesis looked into how websites were viewed from the managerial side of the veterinary practice by conducting in-depth interviews with Online Content Managers (OCMs) from eight veterinary clinics in Fort Collins, CO. The study found that not only did the OCMs find it important to use everything available to them to gain the trust of new potential clients, they also wanted to start and keep an emotional connection with all of their clients via the website. The study also found that the staff and veterinarian biography section of the websites were very important, and that an emphasis was placed on having pictures to go with every staff member, especially if the pictures also had companion animals with the staff members.
Keywords: websites; communications; marketing; telemedicine; veterinary